Disfunción familiar y su incidencia en el consumo de cocaína en un joven de 22 años de edad residente en CETAD Paz del cantón El Empalme - Murillo Cabrera, Julissa Roxana (2022)
This qualitative case study aims to unravel the realities and problems that manifest in a dysfunctional family, which predispose to the development of negative behaviors in family members, as in the case of the patient and the consumption of psychoactive substances. The objective is to determine the incidence of family dysfunction in the cocaine consumption of a 22-year-old young man resident of CETAD "PAZ" in the canton of El Empalme. Hence, to reach the patient's diagnosis, different information collection techniques were used, such as the semi-structured interview, clinical history, and clinical observation and added to this the psychometric tests: OMS-ASSIST V3.0, Mayo Test and the Beck-II Depression Inventory (BDI-II). Likewise, a therapeutic scheme was proposed aimed at working with the symptomatology presented by the patient, which is based on Cognitive Behavioral Therapy. Obtaining satisfactory results in the intervention performed, since the reduction of negative symptoms in the patient was achieved. According to the study, it was concluded that family dysfunction does affect the development of addictive behavior; however, there are other elements that also contribute to this and other risk behaviors.